Parallel Resonance Fault Current Limiter for DFIG Wind Turbine Transient Stability - RULI AMAR MA’RUF; ZULMIFTAH HUDA; HERRI GUSMEDI (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2026)
The increasing penetration of renewable energy, especially wind energy based on Dubly Fed Induction Generator (DFIG), poses challenges in maintaining power system stability. One mitigation approach is the use of a Parallel Resonance Fault Current Limiter (PRFCL), which can limit fault currents and dampen oscillations during major disturbances. This study uses MATLAB/Simulink to simulate a DFIG-integrated IEEE 9 Bus system and evaluate the impact of PRFCL on transient stability during three-phase-to-ground faults. The results show that PRFCL significantly reduces voltage and power deviations, accelerates frequency recovery, and improves the Fault Ride-Through (FRT) capability of DFIG systems.